The association between cytokines and insulin sensitivity in Iraqi immigrants and native Swedes - Memon, Ashfaque A (BMJ Publishing Group, 2013)
OBJECTIVES: To investigate the associations between cytokines and insulin sensitivity in Swedish residents born in Iraq and Swedish residents born in Sweden. DESIGN: Cross-sectional study. SETTINGS: Iraqi and Swedish origin residents of Rosengård area of Malmö, aged 45–65 years, were randomly selected from the census register. PARTICIPANTS/METHODS: 194 (Iraqi, n=107; Swedish, n=87) participants agreed to participate in the study. Nineteen participants dropped out (Iraqi, n=11; Swedish, n=8). Participants who had already been diagnosed with type 2 diabetes mellitus (T2DM), those who could not participate in an oral glucose tolerance test and those who had a cold/fever at the time of blood sampling were excluded. In total, serum samples from 135 individuals of Swedish (n=62) and Iraqi (n=73) origin were included. Serum concentrations of a panel of 10 cytokines, comprising interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12 (p70), IL-13, interferon-γ and tumour necrosis factor-α were analysed by Luminex multiplex assay. RESULTS: In the whole study population, levels of all tested cytokines were inversely associated with insulin sensitivity index (ISI), independent of age, sex, body mass index (BMI), sedentary lifestyle and family history of T2DM (p ≤ 0.05). Interestingly, stratification of the study population according to country of birth showed a significant inverse association between all tested cytokines and ISI in the Iraqi-born population (p ≤ 0.01). The association was independent of age, sex, BMI, sedentary lifestyle and family history of T2DM. In contrast, with the exception for IL-6 (p=0.05), no other tested cytokine was found to be significantly associated with ISI in the Swedish-born population (p≥0.05). CONCLUSIONS: Our results show an association between cytokines and ISI in the Iraqi-born population but not in the Swedish-born population.